Answer:
-3
Explanation:
Let the first term be a-d, second term be a and third term be a+d
d is the common difference
If each term, starting with the 3rd term, is found by multiplying the previous two terms then:
a(a-d) = a+d
a²+ad-a-d = 0
a(a+d)-1(a+d) = 0
(a+d)(a-1) = 0
a-1 = 0
a= 1
a+d = 0
1+d = 0
d = 0-1
d = -1
Get the sixth term
nth term of a sequence is expressed as
Tn = a+(n-1)d
T6 = 1+(6-1)(-1)
T6 = 1+5(-1)
T6 = 1-5
T6 = -4
Get the third term T3
T3 = a+2d
T3 = 1+2(-1)
T3 = 1-2
T3 = -1
difference between the 6th and 3rd terms in the sequence is expressed as;
Difference = T6-T3
Difference = -4-(-1)
Difference = -4+1
Difference = -3